Legal Regulation of Ensuring Human Rights in Ukraine During The Introduction of Martial Law: Constitutional, Administrative and Theoretical Aspects - Kantor, Nataliia; Ivantsova, Zoia; Darahan, Valerii; Velkov, Anatolii; Andreiev, Dmytro (Jurnal Cita Hukum, 2024)
The purpose of the article is to reveal the provision of human rights in Ukraine under the conditions of martial law. Human rights and freedoms are the highest value, but their characteristic feature, as a fundamentally important feature of a progressive society, consists in historical instability, variability and subordination to socio-economic processes in the state, which contradicts the established principles of humanism but remains typical in war conditions. Within the scope of the scientific study, it was determined that human rights have a characteristic of evolution together with society and the state, and therefore, taking into account the complexity of the events taking place on the territory of modern Ukraine, the study of the available range of problems has a particularly important scientific and practical role. A study of the available range of problems was carried out using comparison, abstraction, analysis, and generalization methods. In the course of the study, the essential characteristics of the social category were determined, particularly the theoretical and methodological foundations of ensuring observance of human rights in conditions of martial law (the regulatory and legal basis). Summarizing the events taking place in Ukraine as a result of the treacherous armed aggression of the Russian Federation, it was concluded that under conditions of war, human rights are of the highest value.